Exploring User Experiences of Active Workstations: A Case Study of Under Desk Elliptical Trainers - Choi, Woohyeok; Song, Aejin; Edge, Darren; FUKUMOTO, Masaaki; Lee, Uichin (Proceedings of the 2016 ACM International Joint Conference on Pervasive and Ubiquitous Computing, 2016)
Prolonged inactivity in office workers is a well-known contributor to various diseases, such as obesity, diabetes, and cardiovascular dysfunction. In recent years, active workstations that incorporate physical activities such as walking and cycling into the workplace have gained significant popularity, owing to the accessibility of the workouts they offer. While their efficacy is well documented in medical and physiological literature, research regarding the user experience of such systems has rarely been performed, despite its importance for interactive systems design. As a case study, we focus on active workstations that incorporate under desk elliptical trainers, and conduct controlled experiments regarding work performance and a four week long field deployment to explore user experience with 13 participants. We investigate how such workouts influence work performance, when and why workers work out during working hours, and the general feelings of workers regarding usage. Our experimental results indicate that while work performance is not influenced, the cognitive load of tasks critically influences workout decisions. Active workstations were alternatively used as mood enhancers, footrests, and for fidgeting, and there exist unique social and technical aspects to be addressed, such as noise issues and space constraints. Our results provide significant implications for the design of active workstations and interactive workplaces in general.